P-021 Endovascular treatment of wide necked intracranial aneurysms using microcatheter protective technique: techniques and outcomes in 71 aneurysms. (16th November 2010) - Lee, J; Cho, Y; Kwon, B; Han, M
Abstract : Introduction: Catheter protective technique, an adjunctive technique of multiple microcatheter techniques, means positioning an additional microcatheter, instead of a balloon or stent, in the parent or side branching arteries to protect them during coil embolization. The purpose of this study was to describe a microcatheter protective technique and to evaluate the radiologic and clinical outcomes. Materials and methods: From January 2003 to January 2010, 330 patients harboring 336 wide neck aneurysms were treated with detachable coils using multiple microcatheter techniques. 71 (21.1%) of 336 aneurysms were treated with a catheter protective technique. The aneurysms were in the following locations: middle cerebral artery (22, 31%), anterior communicating/anterior cerebral arteries (17, 23.9%), basilar artery bifurcation (13, 18.3%), posterior communicating artery (nine, 12.7%), anterior choroidal artery (four, 5.6%), internal carotid artery bifurcation (three, 4.2%), vertebral/posterior inferior cerebellar arteries (two, 2.8%) and posterior cerebral artery (one, 1.4%). Ten (14.1%) aneurysms were presented with subarachnoid hemorrhage and 61 (85.9%) were unruptured. The mean aneurysm neck size was 3.9±1.7 mm (range 1.9–13.8 mm) and the mean dome to neck ratio was 1.1±0.3 (range 0.7–2.8). Imaging follow-up, including plan radiography, magnetic resonance angiography or digital subtraction angiography, ranging from 3 to 36 months, was available in 57 (80.3%) patients, with a mean of 14.7±8.8 months. Immediate postprocedural completion angiograms were evaluated using a conventional angiographic scale. Clinical evaluations were performed using a Glasgow outcome scale. Results: Immediate postprocedural angiograms demonstrated total occlusion of the aneurysm in 42 (59.2%) aneurysms, neck remnant in 16 (22.5%) and body filling in 13 (18.3%). There were 11 (15.5%) thromboembolic events that were treated with intra-arterial infusion of tirofiban. One (9%) of these 11 patients had a permanent neurologic deficit (sensory dysphasia). There was no significant difference in the rate of thromboembolic events between the parent artery protecting and side branching artery protecting groups (11.1% vs 17.6%; p=0.71). One patient died and the other patient was severely disabled from complications which were not related to the procedure, secondary to subarachnoid hemorrhage. All patients, except three complicated cases mentioned above, showed excellent clinical outcomes. Of the 57 aneurysms with follow-up, recanalization was developed in five (8.8%) aneurysms, and three (5.3%) cases of major recanalization were retreated endovascularly. Conclusion: The microcatheter protective technique is feasible and safe for coil embolization of wide neck aneurysms, especially in cases which are not suitable for the multiple catheter technique, balloon remodeling technique or stent assisted technique.